Atributes of waiting room in dental clinic for positive feeling on dental patient - 246170 Lim, Wee Ling (Skudai : Universiti Teknologi Malaysia, 2008)
Topical Study (Sarjana Muda Senibina) - Universiti Teknologi Malaysia, 2008